The measurement of collaborative culture in secondary schools: An informal subgroup approach - Meredith, Chloé; Moolenaar, Nienke M; Struyve, Charlotte; Vandecandelaere, Machteld; Gielen, Sarah; Kyndt, Eva (Frontline Learning Research, 2017)
Research on teacher collaboration underlines the importance of a collaborative culture for teachers’ functioning. However, while scholars usually regard collaborative culture as a school team characteristic, this study argues that subgroups may be more meaningful units of analysis to conceptualize and assess teachers’ perceptions of collaborative culture. Based on the assumption that collaborative culture is developed, expressed, and maintained in frequent work-related interactions, this study hypothesizes that collaborative culture is not homogenously spread over the school but rather varies between informal subgroups. Data from 760 Flemish teachers were examined using social network analysis and consensus analyses. The results provided evidence that perceptions on collaborative culture are more homogeneous within informal subgroups that are characterized by frequent interactions than the entire school team. This finding stresses the importance of assessing the meaningful unit of analysis for collective-level and socially-constructed concepts, such as collaborative culture. Moreover, the benefits and potential of a social network approach to identify (socially stable) subunits within the school team are illustrated.